Gamma irradiated LDPE in presence of oxygen. Part I. Non-isothermal crystallization. - Alvarez, Vera Alejandra (2013)
Non isothermal crystallization of low density polyethylene (LDPE) samples irradiated under three different atmospheres was analyzed. The used doses were between 33 and 222 kGy and the atmospheres content 0, 21 and 100% of oxygen. At a given radiation dose, the amount of produced gel is higher when the oxygen content present in the radiation process is lower. The temperature and the enthalpy of crystallization of the modiﬁed polymer decreased almost linearly with the radiation dose. Different classic models were used to predict the development of the relative degree of crystallinity (in the range 0.01?0.3 crystallinity fraction) as a function of temperature and several parameters were analyzed. The values of half-time of crystallization (t1/2) and the parameter Z, from Avrami?s method which characterize the kinetics of non-isothermal crystallization, showed that the crystallization rate, at the same cooling rate, decreased with increasing radiation dose and, at the same dose, with the decrease in the oxygen content. The activation energy for crystallization increased with the radiation dose and with the reduction of the oxygen content, indicating that the increment in molecular crosslinking restricts the crystallization process.